CAN CORPORATE BE SCIENTIFICALLY ASCERTAINED. - Kelley, Arthur C. (The Accounting Review, 1951)
Abstract There is a present need to devise and establish by authoritative recommendations of the profession a set of accounting concepts and standards, which will be generally accepted and adhered to in the determination of corporate net incomes, so that the findings of the accountant as expressed in the annual reports of American corporations with regard to the amount of the income accrued or loss sustained during the fiscal period, will be accepted and relied on by the public and all interested parties as definitive and conclusive and expressing substantially the facts and the result of the events which took place during the period. In the opinion of many accountants such a codification of standards for income calculations would be an important step forward toward allaying the suspicion and lack of faith in the income determinations presented in corporate financial reports. The great usefulness and social utility of such a development in the accounting profession can hardly be questioned, because if it can be achieved it will help to lay the factual foundation for impartial social control if national economy. It is true that in the determination of corporate income for any period of time opinions and estimates play an important part in greater or less degree, depending on the kind of business and the nature of assets.